Electro-Assisted Optical Method of Chirp Compensation for Bandwidth/Bitrate Variable Transceivers Using the Hammerstein-Wiener System - Mumtaz Ali; Michela Svaluto Moreolo; Laia Nadal; Josep M. Fabrega (IEEE Access)
To meet the increasing demand for higher data rates and energy-efficient optical communication networks, this study investigates the unique characteristics of directly modulated (DM) vertical-cavity surface-emitting laser (VCSEL)-based bandwidth/bitrate variable transceivers (BVTs), identifying the critical impact of chirp on system performance. The core contribution of this paper lies in the introduction and exploration of trained Hammerstein-Wiener system model as a novel approach for the chirp compensation in DM VCSEL-based BVTs by considering tailored experimental adaptive digital signal processing blocks in the numerical simulations. With this approach, the system performance is evaluated with direct and coherent reception up to 80 km standard single mode fiber. The DM VCSEL-based BVT with modulation bandwidth of 20 GHz provides an energy-efficient solution with required optical signal-to-noise ratio values between 32.6 and 24 dB for the transmission of double-sideband and single-sideband signals over 40 and 80 km with achieved capacities of 50 and 45 Gbps at $4.62· 10{^{\text {-3}}}$ bit error rate with 7% overhead hard decision-forward error correction limit.